REAKTIVASI SESAR TUA DAN PENGARUHNYA TERHADAP PEMBENTUKAN STRUKTUR GEOLOGI DAN CEKUNGAN KUARTER DI DAERAH BANDUNG-GARUT - -, Edy Sunardi (Fakultas Teknik Geologi Universitas Padjadjaran, 2014)
The geological structure of faults on the pre-Tertiary basement rocks in West Java is the result of the activity of plate collision in the Cretaceous and Tertiary Age. The NE-SW direction of structural pattern is the pattern of major fault related to Cretaceous subduction, while other direction is related to Tertiary. The reactivation fault turned out to continue in Late Tertiary to Quaternary period. Baribis Fault, Cimandiri Fault, and Citanduy Fault which are formed in the Late Tertiary, faulted also Quaternary volcanic rocks.Some Quaternary structures forming sub-basin and heights, which shows genetically similar with its basement rocks. From subsurface geological data, the high and low patterns show similarity to the surface condition, such as under Bandung and Garut depressions, where horst and graben are found. Based on this finding, it can be concluded that there is fault reactivation from basement rocks to the surface.